Faktor yang Mempengaruhi Akseptor Kb dalam Memilih Alat Kontrasepsi - Saniasa Luba; Rukinah Rukinah (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction; family planning is an action that helps individuals or married couples to achieve certain goals in order to avoid unwanted births. Objectives; know the factors that influence family planning acceptors in choosing contraception. Method; using a mixed-method. Quantitative design is used to determine factors of knowledge, education, age, and husband's support. Data collection comes from primary and secondary data, the data collection method used is a questionnaire. Result; That the four variables together do not have a significant effect on the use of non-hormonal contraceptives with an opportunity of 0.2776> 0.05. The magnitude of the influence of the four independent variables together can be seen from the Pseude R-value of 13%. Conclusion; that the factors of age, education, knowledge, and husband's support did not have a significant effect on the choice of contraceptives.